A standardised fraction 1 (SF1) from clinacanthus nutans attenuates the stemness of cervical cancer stem-like cells via inhibition of notch1 signalling - Ismail, Faridah (2024)
Cancer stem cells (CSCs) represent a tiny subset of cancer cells characterised by deregulated self-renewal, aberrant stemness signalling pathways, and a high tumorigenic potential. Mounting evidence indicates that CSCs play a critical role in cancer growth, metastasis, relapse, and resistance to radiotherapy and chemotherapy. Hence, targeting CSCs will provide novel treatments for cancer. Clinacanthus nutans (C. nutans), or locally known as Sabah snake grass (‘daun belalai gajah’), is a well reputed medicinal herb in East Asia that has shown promising anticancer activities in a range of cancer cell types. However, no study has reported its effect on CSCs. Therefore, this study was conducted to determine the antitumour effect of SF1, a semi-purified fraction from C. nutans, on CSCs derived from cervical cancer (CCSCs) and the underlying mechanisms. Bioassay guided fractionation was employed for the isolation of SF1 from C. nutans leaf extract. The SiHa cell line was used for the enrichment of CCSCs by culturing the cells in CSC-conditioned medium (cervospheres). Stemness characterisation of the cervospheres was performed using a sphere formation assay and flow cytometric analysis of the stem-related markers, including CD49f, CK17, Sox2, Nanog, and Oct4. The cervospheres were then subjected to SF1 treatment, and cisplatin was used as a positive control. The antitumour effects of SF1 on cervospheres were evaluated by assessing cell viability, sphere-forming efficiency, and tumorigenic capacity using the OZ blue cell viability kit, sphere formation assay, and in vivo tumorigenicity assay, respectively. The mechanisms by which SF1 eliminated CCSCs were determined by evaluating the selected stemness marker expressions via flow cytometry. Additionally, Notch1 signalling activity, a key regulator for CSC self-renewal and tumorigenicity was examined using the Western blot, quantitative reverse transcriptase PCR (RT-qPCR), and immunohistochemistry staining assays. The results of the study showed that SiHa derived cervospheres exhibited high sphere-forming efficiency, and increased expressions of the stemness markers. In addition, further investigation revealed that these cells possessed higher tumorigenicity in nude mice and increased levels of Notch1 protein and gene expression compared to the parental SiHa monolayer cells. SF1 effectively inhibited the cervosphere viability and stemness phenotypes in vitro and in vivo. SF1 was found to induce a concentration-dependent cytotoxicity in the cells, with a half-maximal inhibitory concentration (IC50) of 17.07 µg/ml. Additionally, treatment of cervospheres with SF1 at the IC50 dose for 72 hours resulted in a significant reduction in the sphere-forming efficiency and a suppression of tumour growth in xenotransplant mice. Besides, SF1 decreased the expression of stemness markers in the cervospheres, primarily CK17 and Sox2 expressions. Nevertheless, Nanog expression remained unaffected. Apart from that, the inhibition of cervosphere stemness properties was accompanied by a marked decrease in the level of Notch1 protein expression. In contrast, increased expression of the Notch1 gene was noted. This implies that SF1 may act by promoting proteasomal degradation of Notch1 protein or disrupting its translation process. In conclusion, SF1 possesses antitumor activity against SiHa derived CSCs, which was achieved through attenuation of their stemness properties and inhibition of the Notch1 signalling. Hence, SF1 may serve as a prospective therapeutic agent for improving cervical cancer management.